Training Program for Good Clinical Practices. - Dalal, Roda; Raut, Ashwinikumar (Indian Practitioner, 2023)
This is a report of the webinar on Good Clinical Practices (GCP) jointly organized by Kasturba Health Society’s Medical Research Centre and Inter System Biomedica Ethics Committee. The training was organized in six scientific sessions arranged over two half days. The delegates for this webinar were from the faculties of Nutrition, Ayurveda, Life Sciences, Pharmacy, Pharmacology, and Clinical Science. The program had prominent national authorities in the domain of ethics and clinical research, who delivered opening remarks. This was followed by scientific sessions on pharmaceuticals, phytopharmaceuticals, Ayurceuticals, nutraceuticals, and dietary supplements. A special session was dedicated to the informed consent form (ICF). The final session was a panel discussion on diagnostics, non-drug therapies, medical devices, quality control, clinical trials & safety monitoring. This write-up gives the gist of the presentation made by various experts.